Treatment of Sarcoptic Mange in Wombats With Topical Moxidectin - Hayley J. Stannard; Marie B. Wynan; Ray J. Wynan; Amanda Cox; Howard Ralph; Gregory S. Doran (Veterinary Medicine and Science)
ABSTRACT Sarcoptic mange is a debilitating disease affecting free‐living/wild bare‐nosed wombats (Vombatus ursinus). The disease causes thickening of the skin, pruritus, alopecia and deep fissures in the skin of infected animals, and ultimately death if left untreated. In Australia, there are approvals from the Australian Pesticides and Veterinary Medicines Authority to use moxidectin for treating sarcoptic mange in bare‐nosed wombats; however, few published literatures document the success of treatment regimens. Two adult male bare‐nosed wombats presented with dermatitis, erythema and crusting of the skin. Evaluation of skin scrapings confirmed the presence of live Sarcoptes scabiei. Both wombats were treated with three 100‐mL doses of moxidectin topically poured on to the dorsal backline approximately 7 days apart. Both animals showed improvement, with skin becoming clear of crusting and dermatitis, and no S. scabiei mites were present on either animal after 2 weeks. Here, we presented two clinical scenarios of sarcoptic mange in wombats that were successfully treated with three 100‐mL doses of moxidectin applied topically. We recommend this treatment be used where wombats can be identified and monitored throughout their recovery.